Parenting Styles as a Predictor of Adolescents’ Career Making Difficulties in Secondary Schools in Anambra State - Onyekwere, O. I.; Nwosu, K. C. (Journal of Guidance and Counselling Studies, 2024)
The study adopted correlational research design to investigate parenting styles as a predictor of adolescents’ career making difficulties in secondary schools in Anambra state. Two research questions and one null hypothesis guided the study. The population comprised all the 8,498 senior secondary school III students (SSS III) in all the 261 public secondary schools in Anambra State. The sample size for this study consisted of 1,125 SSS III students drawn through proportionate stratified sampling technique. Two instruments were used for this research work. The first instrument is titled “Parenting Scale Inventory by Abdul-Gafoor and Abidha (2014) (Adopted); the second instrument is Career Decision-Making Difficulties Questionnaire-Revised (CDDQ) by Gati and Saka (2001) (Adapted). The instruments were validated by Specialists in Education. The reliability of the instrument was determined using Cronbach alpha and an alpha coefficient of 0.78 was obtained. Instrument for data collection was administered by the researchers’ with the aid of 6 research assistants. The result of the study revealed among others that there was weak relationship among parenting styles and students’ career decision-making difficulties in secondary schools in Anambra State. Based on the findings the researchers recommended enhancing career guidance programs in secondary schools which should focus on providing comprehensive information, resources, and opportunities for students to explore diverse career paths independently.